Unpacking the Figure of the Artist-Fieldworker - Dash, Kathyayini (Arts Research Africa (ARA), 2020)
This paper argues that the meeting of practice and academic scholarship constructs the figure of the artist-fieldworker in critical ways, while also giving rise to particular kinds of ethical, formal, and procedural questions of art-making and research.
Arts Research Africa Conference Proceeding 2020
Keywords: Artistic research; Arts research; Decolonisation; Arts pedagogy